Manajemen Risiko Usaha Berbasis Ikan Lele dengan Mempertimbangkan Analisis Biaya - Yudha Adi Kusuma; Dody Susilo (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2024)
Catfish farming is one of the most promising businesses. The potential of the catfish business is influenced by the paradigm shift in fish consumption. The development of catfish businesses is also experienced by catfish farmers in the Madiun Regency area of East Java. There are three phases to catfish farming: breeding, cultivation, and processing. In each phase of catfish farming, there will be potential risks and losses. Potential risks need to be assessed in risk management. The stages of risk management include risk identification, risk assessment, and risk control. The risk identification stage has 63 risk subcriteria. The results of the assessment of the risk sub-criteria showed that seven sub-criteria were categorized as high risk. Handling high-category risks formed 24 alternative strategies in the contingency plan. In addition to handling the risk, the catfish farming business was also analyzed. The results of the analysis of the catfish farming business obtained by the processing phase resulted in the highest total profit, reaching Rp 31,950,000. The results of the catfish farming business analysis are expected to contribute to alternative business choices based on cost indicators.